Telaah Struktur Naratif pada KKPK Ibuku Chayank, Muach Karya Penulis Cilik Izzati - Dian Nathalia Inda; Dedy Ari Asfar (tuahtalino, 2016)
Today, children literature no longer  written by  adults, but children can share their creativity and imagination in this literature. Some publishers accommodate this creativity by publishing children books  named PCPK and KKPK. Children books is very interesting because it is written, read and enjoyed by children. In writing the story, the children have different styles with adults. They reveal things according to their own world. In that regard, not an anomaly if the writer want to analize it,  especially in terms of narrative structure and children literature genre in KKPK. The purpose of this study to examine the narrative structure and children literature genre in the stories of  Ibuku Chayank, Muach! This study used descriptive qualitative method. Sources of data in this study is the short story Ibuku Chayank, Muach! written by young writers, Izzati. The results of this study indicate a narrative structure in any event intertwined with slick and straightforward. One event to another is presented with a sequence so that readers can easily understand the story. Genre Ibuku Chayank, Muach! is realism because  Ibuku Chayank, Muach ! tells about the life that happens in real life.